Daya terima sensori sprinkle berbahan dasar ikan gabus, kacang hijau dan labu kuning untuk mencegah stunting pada balita - Lusiana, Sanya Anda; Sirait, Rosmaida; Kadiwaru, Since; Rosmiati, Risti (ARGIPA (Arsip Gizi dan Pangan), 2025)
Stunting remains a significant nutritional challenge in Indonesia, particularly in Papua, where the prevalence reached 24.8% in 2023. Developing nutrient-rich local food products is one approach to combating stunting. This study aimed to evaluate the sensory acceptability of sprinkles made from snakehead fish, mung beans, and pumpkin as a preventive measure against stunting in toddlers. The sprinkle product was formulated using various combinations of snakehead fish flour, mung beans, and pumpkin, and its acceptability was assessed through hedonic testing by semi-trained panelists. The results indicated that the F25 formula (45 g snakehead fish, 30 g mung beans, 10 g pumpkin) received the highest score for taste attributes and was selected as the preferred formula. This formula is expected to be further developed as a functional food product that can contribute to the prevention of stunting in toddlers in Indonesia by increasing protein intake and other essential nutrients.